2011
DOI: 10.4161/psb.6.12.18024
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid perception and signaling transduction in strawberry: A model for non-climacteric fruit ripening

Abstract: On basis of fruit differential respiration and ethylene effects, climacteric and non-climacteric fruits have been classically defined. Over the past decades, the molecular mechanisms of climacteric fruit ripening were abundantly described and found to focus on ethylene perception and signaling transduction. In contrast, until our most recent breakthroughs, much progress has been made toward understanding the signaling perception and transduction mechanisms for abscisic acid (ABA) in strawberry, a model for non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 31 publications
2
87
0
Order By: Relevance
“…In recent years, not only has ABA been shown to play important roles in perception and signal transduction involved in the regulation of Arabidopsis seed germination, seedling growth, and stomatal movement (Fujii et al ., 2009; Ma et al ., 2009; Melcher et al ., 2009; Miyazono et al ., 2009; Nishimura et al ., 2009; Santiago et al ., 2009; Shang et al ., 2010), but much progress has also been made toward a better understanding of the molecular mechanisms that underlie the roles of ABA in the regulation of fleshy fruit ripening (Chai et al ., 2011; Jia et al ., 2011; Li et al ., 2011; Sun et al ., 2011, 2012). Nevertheless, many ABA signalling components involved in fruit ripening remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, not only has ABA been shown to play important roles in perception and signal transduction involved in the regulation of Arabidopsis seed germination, seedling growth, and stomatal movement (Fujii et al ., 2009; Ma et al ., 2009; Melcher et al ., 2009; Miyazono et al ., 2009; Nishimura et al ., 2009; Santiago et al ., 2009; Shang et al ., 2010), but much progress has also been made toward a better understanding of the molecular mechanisms that underlie the roles of ABA in the regulation of fleshy fruit ripening (Chai et al ., 2011; Jia et al ., 2011; Li et al ., 2011; Sun et al ., 2011, 2012). Nevertheless, many ABA signalling components involved in fruit ripening remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The down-regulation of the expression of ABA receptor genes Mg-chelatase H subunit ( FaABAR/CHLH ) or pyrabactin resistance 1 gene ( FaPYR1 ) can destroy strawberry fruit red colouring, indicating that both FaABAR/CHLH and FaPYR1 proteins are positive regulators of fruit ripening (Chai et al ., 2011; Jia et al ., 2011; Li et al ., 2011). A significant reduction in SINCED1 activity leads to a decline in the transcription of genes encoding major cell wall catabolic enzymes, indicating that ABA affects cell wall catabolism during tomato fruit ripening (Sun et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike what is found in climacteric fruits, experiments with F. × ananassa have shown that ABA is clearly a promoter of ripening in strawberry 108 . VIGS of FaNCED1, encoding a key enzyme in ABA biosynthesis, produced white fruits, and this phenotype was rescued by exogenous ABA 109 .…”
Section: Fruit Developmentmentioning
confidence: 72%
“…ABA can regulate abiotic and biotic stresses in fruit and can also regulate maturation processes in nonclimacteric fruit such as grapes, strawberries (Fragaria × ananassa) and cherries (Prunus avium) (Li et al, 2011;Wheeler et al, 2009;Falchi et al, 2014). ABA treatment increased the pathogen resistance of fruit (Sivakumaran et al, 2016;Lievens et al, 2017).…”
Section: Discussionmentioning
confidence: 99%